2021
DOI: 10.1088/1402-4896/ac1381
|View full text |Cite
|
Sign up to set email alerts
|

Comparing deuterium retention in heavy ion damaged tungsten measured by glow discharge optical emission spectroscopy, nuclear reaction analysis and thermal desorption spectroscopy

Abstract: Hot-rolled tungsten specimen were irradiated with 5 MeV gold ion and loaded with deuterium plasma sequentially. Deuterium retention was examined by glow discharge optical emission spectroscopy, nuclear reaction analysis and thermal desorption spectroscopy. The deuterium depth profiles obtained by nuclear reaction analysis show that deuterium concentration increases significantly after irradiation, and damage region could uptake most of deuterium. The results of thermal desorption spectroscopy demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
(41 reference statements)
5
5
0
Order By: Relevance
“…We find that vacancy concentration saturates well below the dose of 1 dpa, see Fig. 4 a, in agreement with independent simulations 13 , 14 , 16 and experimental observations 32 , 33 . This can be rationalised by recognising that the number of molten atoms per cascade is much higher than the number of ballistically displaced atoms, as suggested by their respective characteristic energy scales .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…We find that vacancy concentration saturates well below the dose of 1 dpa, see Fig. 4 a, in agreement with independent simulations 13 , 14 , 16 and experimental observations 32 , 33 . This can be rationalised by recognising that the number of molten atoms per cascade is much higher than the number of ballistically displaced atoms, as suggested by their respective characteristic energy scales .…”
Section: Resultssupporting
confidence: 91%
“…We compiled nuclear reaction analysis measurements of peak deuterium concentrations in tungsten irradiated to doses dpa under athermal conditions K for a broad range of irradiation energies from a number of studies 33 , 37 40 . For each particle energy represented in the experimental data, we simulated the recoil spectra, see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We find that vacancy concentration saturates well below the dose of 1 dpa, see Fig. 4a, in agreement with independent simulations 13,14,16 and experimental observations 31,32 . This can be rationalised by recognising that the number of molten atoms per cascade is much higher than the number of ballistically displaced atoms, as suggested by their respective characteristic energy scales T d /E melt T d /E d .…”
Section: Defect Content In a Driven Steady Statesupporting
confidence: 92%
“…First-principles simulations found that the deuterium binds preferentially to void surfaces, with a single tungsten vacancy trapping up to 5 deuterium atoms with trapping energies above 1.1 eV 41 . We compiled nuclear reaction analysis measurements of peak deuterium concentrations in tungsten irradiated to doses φ 0.3 dpa under athermal condition T < 500 K for a broad range of irradiation energies from a number of studies 32,[36][37][38][39] . For each particle energy represented in the experimental data, we simulated the recoil spectra, see Fig.…”
Section: Experimental Validationmentioning
confidence: 99%
See 1 more Smart Citation